Incidence and Predictors of Adverse Drug Events Among People Receiving Drug Resistant Tuberculosis Treatment in Uganda: 8-Year Retrospective Cohort Study - Nasasira M; Kalyango JN; Mupere E; Baluku JB (Dove Medical Press, 2022)
Marble Nasasira,1 Joan N Kalyango,1,2 Ezekiel Mupere,3 Joseph Baruch Baluku4,5 1Clinical Epidemiology Unit, Makerere University College of Health Sciences, Kampala, Uganda; 2Department of Pharmacy, Makerere University College of Health Sciences, Kampala, Uganda; 3Department of Paediatrics and Child Health, Makerere University College of Health Sciences, Kampala, Uganda; 4Division of Pulmonology, Kiruddu National Referral Hospital, Kampala, Uganda; 5Makerere University Lung Institute, Kampala, UgandaCorrespondence: Marble Nasasira, Tel +256 778443346, Email marblenasasira@gmail.comBackground: Adverse drug events (ADEs) are regarded as the most essential therapeutic issue during management of drug-resistant tuberculosis (DR-TB) due to the long duration of therapy and concurrent use of many second-line medications. This study aimed to determine the incidence and factors associated with ADEs among patients receiving DR-TB treatment at Mulago hospital in Uganda.Methods: A retrospective cohort study was conducted among 417 DR-TB patient records at Mulago National Referral Hospital from January 2013 to December 2020. Using the data abstraction form, data were collected on socio-demographic and clinical factors, adverse drug events and treatment follow-up time. Data were double entered in Epi data version 3.2 and later exported to Stata version 14.0 for analysis. The incidence rate of adverse drug events was computed using number of cases of ADE divided by overall patient follow-up time. Poisson regression model was used to determine the factors associated with ADEs. The predictors were considered significant at if p< 0.05.Results: The overall incidence was 5.56 ADEs per 100 person months (95% confidence interval (CI) 5.01, 6.15). Treatment regimens containing an aminoglycoside (incident rate ratio (IRR) 1.106, 95% CI 1.005- 1.216 p=0.0391), linezolid (IRR 1.145, 95% CI 1.008- 1.229 p = 0.037) or pyrazinamide (IRR 1.226, 95% CI 1.072- 1.401 p = 0.003) and the treatment duration (in months) (IRR 1.005, 95% CI 1.001- 1.010 p = 0.042) were associated with ADEs.Conclusion: Regimens containing aminoglycosides, linezolid, or pyrazinamide and increase in treatment duration (months) were associated with an increased risk of ADEs. Clinicians should quickly adopt all oral shorter treatment regimens to obviate the need for aminoglycosides and reduce exposure duration.Keywords: adverse drug events, drug-resistant tuberculosis, Uganda